2021
DOI: 10.1093/ecco-jcc/jjab076.652
|View full text |Cite
|
Sign up to set email alerts
|

P530 Proactive therapeutic drug monitoring of anti-TNF agents is associated with higher mucosal healing rates in Crohn’s disease

Abstract: Background Reactive therapeutic drug monitoring (TDM) is routinely used in managing secondary loss of response to anti-TNF agents. Proactive TDM use has been associated with better clinical outcomes but its use in routine practice is still controversial. We aimed to investigate whether using proactive TDM strategy will result in higher mucosal healing and clinical remission rates. Methods After review of electronic case files… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Bossuyt et al 30 found that 52% achieved endoscopic remission in the proactive group, versus 79% in the reactive. Brinar et al 44 found that a higher proportion achieved endoscopic remission in the proactive group (52.4% vs. 42.2%), but this was not statistically significant. There was not enough data, however, to metaanalyse proactive vs reactive TDM.…”
Section: Effects Of Therapeutic Drug Monitoring On Endoscopic Remissionmentioning
confidence: 91%
See 3 more Smart Citations
“…Bossuyt et al 30 found that 52% achieved endoscopic remission in the proactive group, versus 79% in the reactive. Brinar et al 44 found that a higher proportion achieved endoscopic remission in the proactive group (52.4% vs. 42.2%), but this was not statistically significant. There was not enough data, however, to metaanalyse proactive vs reactive TDM.…”
Section: Effects Of Therapeutic Drug Monitoring On Endoscopic Remissionmentioning
confidence: 91%
“…Nine were RCTs 17,19,20,[29][30][31][32][33][34] and the remaining were cohort studies. There were four prospective cohort studies, [35][36][37][38] 11 retrospective cohort studies [6][7][8]18,27,[39][40][41][42][43][44] and two that were both prospective and retrospective cohort studies. 5,45 Table 1 shows a summary of the studies.…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations